X-Ray, Optical, and Infrared Detectors for Astronomy X 2022
DOI: 10.1117/12.2627285
|View full text |Cite
|
Sign up to set email alerts
|

First tests of a 1 megapixel near-infrared avalanche photodiode array for ultra-low background space astronomy

Abstract: Spectroscopy of Earth-like exoplanets and ultra-faint galaxies are priority science cases for the coming decades. Here, broadband source flux rates are measured in photons per square meter per hour, imposing extreme demands on detector performance, including dark currents lower than 1 e-/pixel/kilosecond, read noise less than 1 e-/pixel/frame, and large formats. There are currently no infrared detectors that meet these requirements. The University of Hawai'i and industrial partners are developing one promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At 15V bias there were only 36 pixels showing excess noise as shown in Figure 11. Preliminary results on the engineering samples 13 of 1kx1ks showed that at 50K the thermionic dark current was than 0.1 e/ks/pixel where a ks = 1000 s and the measurement was probably still residual glow. With the maximum usable avalanche gain, the read noise of two electrons was limited by a glow source during readout, traced to a sneak path through the metal layers.…”
Section: Avalanche Gain Of 40xmentioning
confidence: 97%
“…At 15V bias there were only 36 pixels showing excess noise as shown in Figure 11. Preliminary results on the engineering samples 13 of 1kx1ks showed that at 50K the thermionic dark current was than 0.1 e/ks/pixel where a ks = 1000 s and the measurement was probably still residual glow. With the maximum usable avalanche gain, the read noise of two electrons was limited by a glow source during readout, traced to a sneak path through the metal layers.…”
Section: Avalanche Gain Of 40xmentioning
confidence: 97%
“…Sdark=Idark+Fdt,$$ {S}_{\mathrm{dark}}={I}_{\mathrm{dark}}+\frac{F}{dt}, $$ where F$$ F $$ is the glow per frame expressed in electrons per read, Idark$$ {I}_{\mathrm{dark}} $$ is the real dark current, Sdark$$ {S}_{\mathrm{dark}} $$ is the effective dark current, and dt$$ dt $$ is the sampling time, the time period between two consecutive reads of the same pixel. Recently, investigations were conducted on dark signal dependence with pixel readout frequency using 1024prefix×1024$$ 1024\times 1024 $$ pixels array Linear‐mode Avalanche Photodiode (LmAPDs) Claveau et al (2022).…”
Section: Glow In Infrared Detector Arraysmentioning
confidence: 99%